An educational intervention to improve health and nutrition literacy in hypertensive patients in Greece - Niki Mourouti; Maria Michou; Christos Lionis; Panagiota Kalagia; Angelos G Ioannidis; Michalis Kaloidas; Vassiliki Costarelli (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Suboptimal control of blood pressure (BP) is a public health challenge in Greece. This educational intervention attempts to improve health literacy (HL) and nutrition literacy (NL) in primary healthcare (PHC) patients with hypertension (HTN). MATERIALS AND METHODS: This was a proof-of-concept (PoC) educational intervention. Twenty-four patients with HTN and low or medium levels of HL agreed to participate in this 6-week educational intervention. The program was delivered by a general practitioner (GP) in group A and by a qualified nurse in group B. Group C was the control group. The levels of HL of NL, adherence to the Mediterranean diet, and perceived stress were assessed using the European Health Literacy Survey Questionnaire 16 (HLS_EU_Q16) and part B (reading a medication label) of the High Blood Pressure-Health Literacy Scale (HBP-HLS), the Nutrition Literacy Scale-Greek (NLS-Gr), the Mediterranean Diet Adherence Screener (MEDAS), and the Perceived Stress Scale (PSS-14), respectively, together with certain socioeconomic, dietary, and lifestyle characteristics. The Kruskal-Wallis and Wilcoxon nonparametric, the Chi-square, and the McNemar-Bowker tests were used. The analysis was done with the STATA software, version 14 (MP & Associates, Sparta, Greece). RESULTS: No statistically significant differences were found in the total score of HL and NL before and after the intervention; however, the results indicate a slight improvement in HL and NL levels in the two intervention groups, together with small improvements in knowledge and behaviors related to HTN and dietary salt. A trend of improvement in the MEDAS levels in the GP's group and the HBP-HLS levels in the nurse's group was also reported. CONCLUSION: A slight improvement in HL and NL levels in the two intervention groups has been reported, and the changes, however, were not statistically significant.